The Effect on Clinical Stress Levels of the Readiness and Acceptance Nursing Students Regarding the Online Learning Method Used in Professional Skills Practice (Bangladesh Journal of Medical Science, 2024)
Objective: The study was conducted with the aim of determining the readiness and acceptance levels and the clinical stress levels of students of a faculty of nursing for online learning in before, during and after clinical practice.Material and method: The descriptive research was executed with 233 students enrolled in the Faculty of Nursing in Izmir, in the western part of Turkey. The data was collected by means of Student Descriptive Characteristics Form,the Online Learning Readiness Scale (OLRS), the Online Learning Acceptance Scale (OLAS) and the Clinical Stress Questionnairre (CSQ). Number-percentage distribution, test/Mann Whitney-U/Kruskal Wallis analysis, Friedman variance analysis were used in the evaluation of the relevant data.Results: The difference between the three different measurements of the OLRS and OLAS were examined, and a statistically significant difference was found between them (X2=14.52, p